Hypoglycaemia risk with insulin degludec compared with insulin glargine in type 2 and type 1 diabetes: a pre‐planned meta‐analysis of phase 3 trials. Issue 2 (3rd December 2012) - Ratner, R. E.; Gough, S. C. L.; Mathieu, C.; Del Prato, S.; Bode, B.; Mersebach, H.; Endahl, L.; Zinman, B.
<x xml:space="preserve">Abstract</x> Aim Hypoglycaemia and the fear of hypoglycaemia are barriers to achieving normoglycaemia with insulin. Insulin degludec (IDeg) has an ultra‐long and stable glucose‐lowering effect, with low day‐to‐day variability. This pre‐planned meta‐analysis aimed to demonstrate the superiority of IDeg over insulin glargine (IGlar) in terms of fewer hypoglycaemic episodes at equivalent HbA1c in type 2 and type 1 diabetes mellitus (T2DM/T1DM). Methods Pooled patient‐level data for self‐reported hypoglycaemia from all seven (five in T2DM and two in T1DM) randomized, controlled, phase 3a, treat‐to‐target trials in the IDeg clinical development programme comparing IDeg once‐daily (OD) vs. IGlar OD were analysed. Results Four thousand three hundred and thirty subjects (2899 IDeg OD vs. 1431 IGlar OD) were analysed. Among insulin‐naïve T2DM subjects, significantly lower rates of overall confirmed, nocturnal confirmed and severe hypoglycaemic episodes were reported with IDeg vs. IGlar: estimated rate ratio (RR):0.83[0.70;0.98]95%CI, RR:0.64[0.48;0.86]95%CI and RR:0.14[0.03;0.70]95%CI. In the overall T2DM population, significantly lower rates of overall confirmed and nocturnal confirmed episodes were reported with IDeg vs. IGlar [RR:0.83[0.74;0.94]95%CI and RR:0.68[0.57;0.82]95%CI). In the T1DM population, the rate of nocturnal confirmed episodes was significantly lower with IDeg vs. IGlar during maintenance treatment (RR:0.75[0.60;0.94]95%CI). Reduction in hypoglycaemia with IDeg vs. IGlar was more pronounced during maintenance treatment in all populations. Conclusions The limitations of this study include the open‐label design and exclusion of subjects with recurrent severe hypoglycaemia. This meta‐analysis confirms that similar improvements in HbA1c can be achieved with fewer hypoglycaemic episodes, particularly nocturnal episodes, with IDeg vs. IGlar across a broad spectrum of patients with diabetes.